Sport-specific use of doping substances: World Anti-Doping Agency analysis of doping control tests between 2014 and 2017 - Aguilar-Navarro, M.; Salinero, J. J.; Muñoz-Guerra, J.; Plata, M. D. M.; Del Coso, J. (Substance Use & Misuse, 2020)
Background: In recent years, there has been a solid effort across all sports organizations to reduce the prevalence and incidence of doping in sport. However, the efficacy of current strategies to fight against doping might be improved by using anti-doping polices tailored to the features of doping in each sport. Objectives: The aim of this investigation was to analyze the substances more commonly found in doping control tests in individual and team sports. Material and Methods: The publicly accessible Testing Figures Reports made available by the World Anti-Doping Agency, were analyzed from 2014 to 2017. Results: The most commonly detected groups of banned substances were anabolic agents and stimulants but the distribution of adverse findings per drug class was very different depending on the sports discipline. Weightlifting, athletics, rugby, hockey and volleyball presented abnormally high proportions of anabolic agents (p=2.8×10-11). Cycling, athletics and rugby presented atypically elevated proportions of peptide hormones and growth factors (p=1.4×10-1). Diuretics and masking agents were more commonly found in boxing, wrestling, taekwondo, judo, shooting, and gymnastics than in other sports (p=4.0×10-68). Cycling, rowing, aquatics, tennis, gymnastics and ice hockey presented abnormally high proportions of stimulants (p=1.8×10-5). Conclusions: These results indicate that the groups of banned substances more commonly detected in anti-doping control tests were different depending on the sports discipline. These data suggest the prohibited substances used as doping agents might be substantially different depending on the type of sport and thus, sports-specific anti-doping policies should be implemented to enhance the efficacy of anti-doping testing.